2016
DOI: 10.1080/00222895.2016.1161591
|View full text |Cite
|
Sign up to set email alerts
|

Neural Efficiency in Expert Cognitive-Motor Performers During Affective Challenge

Abstract: Skilled individuals demonstrate a spatially localized or relatively lower response in brain activity characterized as neural efficiency when performing within their domain of expertise. Elite athletes are experts in their chosen sport and thus must be not only adept in the motor domain but must be resilient to performing under the stress of high-level competition. Such stability of performance suggests this population processes emotion and mental stress in an adaptive and efficient manner. This study sought to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“… 1 = Babiloni et al ( 2009 ); 2 = Babiloni et al ( 2010 ); 3 = Berti et al ( 2019 ); 4= Costanzo et al ( 2016 ); 5 = Del Percio et al ( 2008 ); 6 = Del Percio et al ( 2009b ); 7 = Del Percio et al ( 2010 ); 8 = Del Percio et al ( 2011 ); 9 = Del Percio et al ( 2019 ); 10 = Di Russo et al ( 2005 ); 11 = Duru and Assem ( 2018 ); 12 = Guo et al ( 2017 ); 13 = Hatta et al ( 2009 ); 14 = Iwadate et al ( 2005 ); 15 = Kim et al ( 2014 ); 16 = Kita et al ( 2001 ); 17 = Milton et al ( 2007 ); 18 = Naito and Hirose ( 2014 ); 19 = Nakamoto and Mori ( 2008 ); 20 = Olsson et al ( 2008 ); 21 = Park et al ( 2020 ); 22 = Qiu et al ( 2019 ); 23 = Wang and Tu ( 2017 ), 24 = Wei and Li ( 2017 ); 25 = (Wei and Li, 2018 ); 26 = Yamashiro et al ( 2015 ); 27 = Yang et al ( 2020 ); 28 = Zhang et al ( 2019 ) . fMRI, Functional magnetic resonance imaging; EEG, Electroencephalogram; fNIRS, Functional near-infrared spectroscopy .…”
Section: Resultsmentioning
confidence: 99%
“… 1 = Babiloni et al ( 2009 ); 2 = Babiloni et al ( 2010 ); 3 = Berti et al ( 2019 ); 4= Costanzo et al ( 2016 ); 5 = Del Percio et al ( 2008 ); 6 = Del Percio et al ( 2009b ); 7 = Del Percio et al ( 2010 ); 8 = Del Percio et al ( 2011 ); 9 = Del Percio et al ( 2019 ); 10 = Di Russo et al ( 2005 ); 11 = Duru and Assem ( 2018 ); 12 = Guo et al ( 2017 ); 13 = Hatta et al ( 2009 ); 14 = Iwadate et al ( 2005 ); 15 = Kim et al ( 2014 ); 16 = Kita et al ( 2001 ); 17 = Milton et al ( 2007 ); 18 = Naito and Hirose ( 2014 ); 19 = Nakamoto and Mori ( 2008 ); 20 = Olsson et al ( 2008 ); 21 = Park et al ( 2020 ); 22 = Qiu et al ( 2019 ); 23 = Wang and Tu ( 2017 ), 24 = Wei and Li ( 2017 ); 25 = (Wei and Li, 2018 ); 26 = Yamashiro et al ( 2015 ); 27 = Yang et al ( 2020 ); 28 = Zhang et al ( 2019 ) . fMRI, Functional magnetic resonance imaging; EEG, Electroencephalogram; fNIRS, Functional near-infrared spectroscopy .…”
Section: Resultsmentioning
confidence: 99%
“…22 Neural efficiency refers to the reduced neural activity requirements of experts to perform a learned skill or task relative to novices, suggesting relative magnitude of neural activity scales with expertise and the ability to handle more complex coordination or environmental perturbations. [75][76][77][78] The lack of neural efficiency and associated frontal region activity is corroborated with electroencephalography (EEG), indicating increased frontal theta power during force control and joint position tasks in patients with ACL-R ~one year post-surgery compared to uninjured controls. 20,21 Frontal Theta power is an indicator of focused attention and task complexity, 20 which may indicate that simple knee force control and joint position tasks are more complex and require greater attention for patients with ACL-R. Additionally, EEG has revealed that patients with ACL-D require more cognition/attention resources relative to healthy controls during walking, running and landing tasks as evidenced by significant increases in delta, theta, alpha, and beta band power, as well as asymmetry of the beta band power across the frontal and parietal lobes during jogging and landing.…”
Section: Acl Injury Associated Neurocognitive Motor Planning Brain Activationmentioning
confidence: 99%
“…In another study, table tennis athletes showed less neural activation in task-related brain regions during a go/no-go visual-spatial task (Guo et al, 2017). Athletes also showed less neural activation in prefrontal cortex and insula during affective challenges than controls (Costanzo et al, 2016). These discrepancies may be related to the between-group paradigm (experts vs. novices), which entangles individual differences with neural dynamics.…”
Section: Introductionmentioning
confidence: 99%